Deficits in the thalamocortical pathway associated with hypersensitivity to pain in patients with frozen shoulder - Li, Tengshuai; Li, Jie; Zhao, Rui; Zhou, Jiaming; Chu, Xu (Frontiers in Neurology, 2023)
Abstract Background and Purpose Frozen shoulder (FS) is a chronic pain condition and has been shown to be associated with pain sensitization. However, the underlying brain mechanisms remains unclear. Here, we aim to explore the brain alterations and its association with pain sensitization in patients with FS. Materials and Methods 54 FS patients and 52 healthy controls (HC) were included in our current study. Here, we applied both structural and functional magnetic resonance imaging (MRI) techniques to investigated brain abnormalities in FS patients. Voxel-wise comparisons were performed to reveal the differences in grey matter volume (GMV) and amplitude of low frequency fluctuation (ALFF) between FS and HC. Further, ROI (region of interest) to whole brain functional connectivity (FC) was calculated and compared between group. Last, Pearson correlation coefficients were computed to reveal the association between clinical data and brain alterations. Results Four main findings were observed: (1) FS patients exhibited decreased thalamus GMV which correlated with pain intensity and pain threshold; (2) relative to HCs, FS exhibited higher level of ALFF within ACC and thalamus; (3) FS patients exhibited significant increase in Tha-S1 FC compared to HC; (4) the effect of thalamus GMV on pain intensity was mediated by pain threshold in FS patients. Conclusion Dysfunctional thalamus might induce pain hypersensitivity which further aggravates the pain in FS patients. Keywords Functional Magnetic Resonance Imaging, Chronic Pain, Frozen shoulder, Amplitude of Low Frequency Fluctuation, Grey Matter Volume, Functional Connectivity.